STUDY OF EFFECT OF FISCAL DECENTRALIZATION TO REGIONAL ECONOMIC IMPROVEMENT IN INDONESIA - FAIZAL BANAPON, M.
The existence of paradigm shift in building the region from centralization to decentralization because of the thought that the central government's power is too big on the affairs that should be managed by the local government. The affairs that the local government better understand it. In addition, it is felt to limit the innovation and creativity of the local government to develop its territory in terms of politics and economy. Therefore, it become part of the driving force for the implementation of regional autonomy. Regional autonomy as an approach in develop the region and also expected to improve the economy and provide welfare for people in the region. Based on government policies that change the development approach from centralization to decentralization, it raises the assumption that there is an influence on the improvement of regional economy. In fact so far the influence of fiscal decentralization on regional economic growth is still a long debate. Thera are many fiscal decentralization theories, that support fiscal decentralization gives impact on regional economic growth. On the other hand, however, many study findings are contrary to the usual policy that fiscal decentralization usually generates a positive contribution to economic growth. The purpose of this research is to know the correlation influence of the increase fiscal capacity of region to the improvement of regional economy seen through indicator in PDRB such as household consumption expenditure, expenditure of government consumption, gross fixed capital formation (PMTB), exports and imports. In addition to testing the fiscal component as an independent variable, this study also uses control variables that are expected to affect regional economic improvement. The function of these control variables is to see the consistency of the fiscal component in giving effect to the improvement of the regional economy. The control variables are population, education level, human development index (IPM), and gross fixed capital formation. This research covers 33 provinces in Indonesia with a span of 12 years (2004-2015). Therefore, this study uses panel data as the basic material in conducting the study and using the method of regression analysis of econometric data panel in testing the methematically arranged models. The results of the analysis show that basically the fiscal decentralization instrument which is part of the policy of regional autonomy can give a significant influence to the improvement of regional economy. This is indicated by an increase in regional economic indicators. On the other hand, it should be emphasized that the positive significance of each fiscal component is limited to certain economic indicators, has not consistently been able to influence the improvement of all economic indicators of the region. Particularly the DAU component, although it has a significant influence on the regional economy, but the coefficient is negative. That means, when an increase in the DAU component will reduce the regional economic component of the region. This finding contrary to the logic of efficiency, because the presence of fiscal decentralization components as inputs, should provide an improvement to the region's economy seen through the economic indicators of the area under test.